Hung Nguyen-Viet speaks at the PREZODE side event – FAO Science and Innovation Forum 2022 - Hung Nguyen-Viet (2022)
PREZODE hosted a side event on 13 Oct 2022 within the FAO Science and Innovation Forum. Hung addressed the topic 'Preventing zoonotic disease emergence while ensuring food security and livelihoods for the poorest communities' with a talk focused on the context surrounding the emergence of infectious diseases, and the need to foster multilateral collaboration to implement prevention strategies.